The Role of Strategic Thinking Skills in Building Dynamic Capabilities - Abdul Hussein Gatea, Eftekhar (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the current study was to present different strategic insights by examining the relationship between strategic thinking skills and dynamic capabilities in business organizations and recognizing that relationship by a sample consisting of leaders working in a number of Jordanian telecommunications companies, using the resource-based theory, with the purpose being to identify the role of strategic thinking skills in building dynamic capabilities. The nonprobability sampling method was used, which allows the collection of samples from the available relevant community or group with relative ease. The study sample or community consisted of all senior and middle management staffers (managers, heads of departments, etc.) of the three telecommunications sectors (Orange, Umniah, and Zain), which are regarded as pioneers in this field, with branches covering all Jordanian provinces. The sample included (173) individuals to whom copies of the study’s questionnaire were handed over, with the number of retrieved copies being (147), which makes (76%) of the total number of respondents. The multiple regression technique was used to test the hypotheses of the study. The study results showed a positive relation between strategic thinking skills and dynamic capabilities, with the degree of influence being different from one variable to the other. The study stressed the importance of continuously focusing on thinking skills in using modern methods in building dynamic capabilities through which a company could outperform its rivals."